1984
DOI: 10.1177/019262338401200203
|View full text |Cite
|
Sign up to set email alerts
|

Use of Historical Control Data in Carcinogenicity Studies in Rodents

Abstract: This paper considers the use of historical control data in the evaluation of tumor incidences from carcinogenicity studies in rodents. Although the most appropriate control group for interpretative purposes is always the concurrent control, there are instances in which the use of historical control information can aid an investigator in the overall evaluation of tumor incidence data. One example is rare tumors; another is a tumor that shows a marginally significant result relative to concurrent controls. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(117 citation statements)
references
References 18 publications
6
111
0
Order By: Relevance
“…The National Toxicology Program/National Institute of Environmental Health Sciences (NTP/NIEHS) maintains a computerized data bank, the Toxicology Data Management System (TDMS), comprised of tumor incidences compiled from the NTP's 2-year carcinogenesis studies. The TDMS incorporates 5 to 7 years' worth of data from peer-reviewed studies in which Fischer 344/N (F344) rats or B6C3F 1 mice were utilized (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The National Toxicology Program/National Institute of Environmental Health Sciences (NTP/NIEHS) maintains a computerized data bank, the Toxicology Data Management System (TDMS), comprised of tumor incidences compiled from the NTP's 2-year carcinogenesis studies. The TDMS incorporates 5 to 7 years' worth of data from peer-reviewed studies in which Fischer 344/N (F344) rats or B6C3F 1 mice were utilized (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Historical control data are routinely used by regulatory agencies in the assessment of chronic toxicity and carcinogenicity data. For example, according to the FDA (2001): "Historical control data can also be used as a quality control mechanism for a carcinogenicity experiment by assessing the reasonableness of the spontaneous tumor rates in the concurrent control group (Haseman 1984;Haseman et al 1984) and for evaluation of disparate findings in dual concurrent controls." The use of historical control data, particularly from the same laboratory, is a well-established method used by regulatory agencies and the National Toxicology Program (NTP) for understanding how an animal model performs and for preventing the overinterpretation of results (Keenan et al 2009).…”
mentioning
confidence: 99%
“…Although other ovarian tumors (benign mixed adenoma, adenoma) were also noted, their incidences were low. Generally, in control B6C3F1 mice granulosa cell tumors are the third most commonly encountered ovarian tumors (20) and they are expected to be seen in less than 0.5% of control mice (9).…”
Section: Ovarian Granulosa Cell Tumorsmentioning
confidence: 99%
“…Since brain tumors are rare in mice (9), it was suggested that this may represent a treatment-related effect, especially since these lesions were seen in mice 66 weeks old or less. In the second 1,3-butadiene study, a few brain tumors were also found.…”
Section: Brain Tumorsmentioning
confidence: 99%
See 1 more Smart Citation